Paving the way how we achieve clean, safe and attractive streets : a research project (Thomas Telford, 2002)
This is more than a design manual - instead it examines the decision-making processes that create our current streetscapes. It endeavours to get behind the finished product to understand how and why it was created, how it is cared for, and by doing so, identify the impediments to the creation of good streetscape.